Nanometer composite dielectric film with multi-layer gradient structure and preparation method of nanometer composite dielectric film
By introducing gradient structures and buffer layers into the multi-layer structural dielectric film, the uneven electric field distribution and early breakdown problems caused by dielectric differences are solved, and the breakdown field strength, dielectric constant and energy storage density are improved.
Patent Information
- Application Number
- CN202411429380.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-14
AI Technical Summary
While the existing multi-layer structure dielectric films increase the breakdown field strength and dielectric constant, it is difficult to simultaneously increase the energy storage density, and the dielectric difference between layers leads to uneven electric field distribution, which easily leads to early breakdown.
A nanocomposite dielectric film with a multi-layer gradient structure is symmetrically arranged by symmetrically setting the outer pressure-bearing layer and the inner polarization layer, and a buffer layer is introduced between the two. The buffer layer is P (VDF-HFP) and PMMA mixed in a volume ratio of 60%, and both are filled with Ni(OH)2.
It significantly alleviates the dielectric differences between different functional layers, improves the breakdown field strength and dielectric constant, improves the uniformity of the electric field distribution, and thus significantly improves the energy storage density.
Smart Images

Figure CN119517620A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dielectric capacitors, and in particular to a nano-composite dielectric film with a multi-layer gradient structure and a preparation method thereof. Background Art
[0002] As human demand for energy storage continues to increase, dielectric capacitors have become an ideal energy storage device due to their high power density and ultra-fast charging and discharging speeds. They are widely used in electronic circuits, microwave communications, power systems and other fields and play a vital role. However, its energy storage density and charging and discharging efficiency are relatively low, which causes a sudden increase in the volume and weight of the capacitor and the conversion of undesirable energy losses into heat. This is obviously contrary to the development trend of future energy storage devices to store and release energy efficiently and stably. Therefore, achieving a dual improvement in the energy storage density and efficiency of dielectric capacitors is a persistent pursuit of scientific researchers. The discharge energy density and efficiency of dielectric materials can be defined as:
[0003] Where Pm is the maximum polarization, Pr is the remnant polarization, E is the external electric field, and U is loss is the energy loss. For linear dielectrics, the discharge energy density can be expressed as: Where ε0 is the dielectric constant of vacuum, ε r is the relative dielectric constant of the dielectric material. Obviously, ε r and E b are two important parameters that determine the energy storage density of materials, and E b Compared to ε r The impact is more critical.
[0004] As an energy storage device, dielectric capacitors have the ability of fast charging and discharging and high power density compared to chemical capacitors and batteries, and have been widely used in many advanced power systems. In practical applications, dielectric capacitors will cause an undesirable increase in their own volume and weight due to their low energy storage density, which runs counter to the lightweight and miniaturization of devices. The materials used in dielectric capacitors can be roughly divided into two categories: organic polymers and inorganic ceramics. The former has a higher breakdown field strength and a lower dielectric constant, while the latter has a higher dielectric constant but an unsatisfactory breakdown field strength. It is difficult for both of the above-mentioned dielectric materials to achieve a higher energy storage density alone. Nanocomposite films composed of organic polymers and inorganic ceramic fillers that combine their respective advantages to achieve energy storage performance that exceeds both have great potential for solving this problem. With the deepening of research, it was found that a part of the composite film has a higher breakdown field strength but the dielectric constant cannot reach a higher level when the content is filled at a low level, and the dielectric constant of the other part with a high content of filling increases, and the corresponding breakdown field strength drops sharply, which makes the research on the energy storage density of composite film dielectrics into a dilemma.
[0005] The multi-layer dielectric film, with an insulating layer composed of a breakdown-resistant polymer or a ceramic filler that can block the breakdown path, overcomes the problem of the difficulty in simultaneously increasing the breakdown field strength and the dielectric constant through different functional layers of a pressure-bearing layer with a high breakdown field strength and a polarization layer with a high dielectric constant. However, studies have shown that although the dielectric difference between layers will cause interface polarization, thereby increasing the dielectric constant, it will also cause electric field distortion at the junction of adjacent layers and large dielectric differences between different layers. The uneven distribution of the electric field in an external electric field will lead to early breakdown, which is not conducive to further improving the energy storage density of the dielectric film. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a nanocomposite dielectric film with a multilayer gradient structure and a preparation method thereof, which can significantly alleviate the dielectric difference between different functional layers of the multilayer structure, while improving the breakdown field strength and dielectric constant, and increasing the energy storage density.
[0007] The technical solution adopted by the present invention to solve the above technical problems is: a multi-layer gradient structure nanocomposite dielectric film, including a symmetrically arranged outer pressure-bearing layer and a polarization layer located between the two pressure-bearing layers, the pressure-bearing layer is a mixture of PMMA and P (VDF-HFP) in an equal volume ratio, the polarization layer is P (VDF-HFP), a buffer layer is arranged between the pressure-bearing layer and the polarization layer, the buffer layer is a mixture of P (VDF-HFP) and PMMA in a volume ratio of 60%; the pressure-bearing layer, the polarization layer and the buffer layer are all filled with Ni (OH) 2. The buffer layer is introduced to slow down the electric field mutation caused by the dielectric difference of adjacent layers, thereby improving the breakdown field strength and energy storage density.
[0008] Furthermore, the buffer layer is formed by mixing P(VDF-HFP) and PMMA in a volume ratio of 60%.
[0009] Furthermore, the sum of the thickness of the pressure-bearing layer and the buffer layer on one side is equal to the thickness of the polarization layer.
[0010] Furthermore, the thickness ratio of the pressure-bearing layer to the buffer layer is (1-3): (3-1).
[0011] Preferably, the thickness ratio of the pressure-bearing layer to the buffer layer is 3:1.
[0012] Furthermore, the filling mass percentage of the Ni(OH)2 in the pressure-bearing layer, the polarization layer and the buffer layer is 30% respectively.
[0013] The present invention also provides a method for preparing a multi-layer gradient structure nanocomposite dielectric film, comprising the following steps:
[0014] (1) Preparation of Ni(OH)2 nanosheets by hydrothermal method;
[0015] (2) adding Ni(OH)2 nanosheets to the pressure-bearing layer, the buffer layer and the polarization layer, and performing electrospinning according to the multilayer gradient structure of claim 1;
[0016] (3) A multilayer gradient structured nanocomposite dielectric film is obtained by hot pressing under preset conditions.
[0017] Further, step (1) is specifically as follows: weigh 1.2 g NaOH and 3.565 g NiCl2 and add them to 25 ml deionized water respectively, stir magnetically at 600 r / min for 30 minutes until completely dissolved, then slowly drip the NiCl2 solution into the NaOH solution and add 30 ml deionized water to mix, stir magnetically at 600 r / min for 30 minutes, then pour the uniform mixed solution into a high-pressure reactor, react at 200°C for 24 hours, wash the reaction product with alcohol and deionized water alternately by centrifugation at a speed of 8000 r / min for several times, transfer the product to a vacuum drying oven after washing, dry it at 60°C for 24 hours, and grind it to obtain light green Ni(OH)2 nanosheets.
[0018] Further, step (2) is specifically as follows:
[0019] A. Dissolve Ni(OH)2 nanosheets in N,N-dimethylformamide (DMF), disperse by ultrasonication, and then stir magnetically at 600 r / min for 30 min until the mixture is uniform, to form a Ni(OH)2 nanosheet solution with a concentration of 0.3 g / L;
[0020] B. P(VDF-HFP) and PMMA were added to the Ni(OH)2 nanosheet solution, stirred at 600 r / min magnetic force and 60°C for 2 h, and then stirred at room temperature for 4 h to form a pressure-bearing layer solution with a volume ratio of P(VDF-HFP) to PMMA of 50%;
[0021] C. Add P(VDF-HFP) and PMMA to the Ni(OH)2 nanosheet solution, stir at 600 r / min magnetic force and 60°C for 2 h, and stir at room temperature for 4 h to form a buffer layer solution with a volume ratio of 60%;
[0022] D. Add P(VDF-HFP) to the Ni(OH)2 nanosheet solution, stir at 600 r / min magnetic force and 60°C for 2 h, and stir at room temperature for 4 h to form a polarization layer solution;
[0023] E. The pressure-bearing layer solution, the buffer layer solution and the polarization layer solution are respectively subjected to vacuum treatment to remove bubbles, and electrospun at a rate of 1 mm / min in an environment of a temperature of 40°C and a humidity of 30°C according to the gradient structure sequence described in claim 1, collected on aluminum foil, and then placed in an oven at 60°C for 2 hours to remove residual solvent to obtain a composite film.
[0024] Furthermore, the amount of the Ni(OH)2 nanosheets added to the pressure-bearing layer solution, the buffer layer solution and the polarization layer solution is 30% by mass.
[0025] Furthermore, step (3) is specifically as follows: pasting the composite film prepared in step (2) on the conductive surface of the conductive glass, and hot pressing it in a vacuum vulcanizer at 150°C and a pressure of 15Mpa for 30 minutes. After the hot pressing is completed, the composite film is placed in an oven at 200°C for 10 minutes, and then quickly placed in an ice-water mixture to complete the quenching operation. After cleaning and drying, a multi-layer gradient structure nanocomposite dielectric film is obtained.
[0026] Compared with the prior art, the advantages of the present invention are: a multi-layer gradient structure nanocomposite dielectric film and its preparation method of the present invention, with PMMA-P (VDF-HFP) equal volume ratio blended substrate with high breakdown field strength as the outer layer and P (VDF-HFP) with high dielectric constant as the inner layer, can simultaneously improve the breakdown field strength and dielectric constant of the composite film; the gradient structure dielectric film reduces the dielectric difference of the substrate materials of adjacent layers of the composite material by introducing a buffer layer, and the changes of dielectric constant and conductivity are continuous, so that the electric field distribution inside the material is uniform, and at the same time, due to the increase of interlayer interfaces, the breakdown path is hindered, and the breakdown field strength of the composite film is further improved. Secondly, using Ni (OH) 2 nanosheets as fillers, the vertical electric field distribution of nanosheets with a large aspect ratio can improve the breakdown field strength, and the parallel electric field distribution can improve the dielectric constant. The composite film couples the above functions together, so that the breakdown resistance of the composite film is significantly improved, and the energy storage density of the gradient structure composite film is optimized.
[0027] In summary, the multi-layer gradient structure of the nanocomposite dielectric film and the preparation method thereof of the present invention can achieve a significant improvement in the overall energy storage performance of the composite material, so that it has excellent breakdown resistance and dielectric properties, and the preparation process is green and environmentally friendly, the process is simple, and can be widely used. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The flowchart of the preparation of the multi-layer gradient structure nanocomposite dielectric film;
[0029] Figure 2The scanning electron microscope microscopic morphology of the multi-layer gradient structure nanocomposite dielectric film;
[0030] Figure 3 The curve of the dielectric constant of the multi-layer gradient structure nanocomposite dielectric film changing with frequency;
[0031] Figure 4 The curve showing the change of dielectric loss with frequency of the multi-layer gradient structure nanocomposite dielectric film;
[0032] Figure 5 It is a bar graph of breakdown field strength and energy storage density of nanocomposite dielectric films with multi-layer gradient structure;
[0033] Figure 6 The finite element simulation diagram of the electrical breakdown process of the multi-layer gradient structure nanocomposite dielectric film;
[0034] Figure 7 This is a finite element simulation diagram of the electric field distribution of a multilayer gradient structured nanocomposite dielectric film;
[0035] Figure 8 It is the PE curve of different thickness of pressure-bearing layer and buffer layer in the multilayer gradient structure composite film. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below with reference to the accompanying drawings.
[0037] Polyvinylidene fluoride-hexafluoropropylene copolymer P(VDF-HFP) and polymethyl methacrylate PMMA were purchased from Shanghai Sanaifu New Materials Co., Ltd. DMF N,N-dimethylformamide (AR, 99.5%), NaOH (AR, 99.5%), and nickel chloride NiCl2·6H2O (AR, 99.5%) were bought from Aladdin.
[0038] 1. Specific embodiments Embodiment 1
[0040] A nanocomposite dielectric film with a multilayer gradient structure includes a symmetrically arranged outer pressure-bearing layer and a polarization layer located between the two pressure-bearing layers. The pressure-bearing layer is a mixture of PMMA (polymethyl methacrylate) and P (VDF-HFP) (polyvinylidene fluoride-hexafluoropropylene copolymer) in an equal volume ratio, and the polarization layer is P (VDF-HFP). A buffer layer is arranged between the pressure-bearing layer and the polarization layer, and the buffer layer is a mixture of P (VDF-HFP) and PMMA in a volume ratio of 60%; the pressure-bearing layer, the polarization layer and the buffer layer are all filled with Ni (OH) 2. The sum of the thickness of the pressure-bearing layer and the buffer layer on one side is equal to the thickness of the polarization layer. The ratio of the thickness of the pressure-bearing layer to the buffer layer is 3:1. The specific steps of the preparation method are as follows:
[0041] Step 1: Prepare Ni(OH)2 nanosheets by hydrothermal method, as follows:
[0042] Weigh 1.2g NaOH and 3.565g NiCl2 respectively and add them to 25ml deionized water, stir magnetically at 600r / min for 30 minutes until completely dissolved, then slowly drop the NiCl2 solution into the NaOH solution and add 30ml deionized water to mix, stir magnetically at 600r / min for 30min, then pour the uniform mixed solution into a high-pressure reactor, react fully at 200℃ for 24h, wash the reaction product with alcohol and deionized water alternately by centrifugation at 8000r / min for several times, transfer the product to a vacuum drying oven after washing, dry it at 60℃ for 24h, and grind it to obtain light green Ni(OH)2 nanosheets.
[0043] Step 2: Add Ni(OH)2 nanosheets to the pressure-bearing layer, the buffer layer and the polarization layer, and perform electrospinning according to the multilayer gradient structure of claim 1, as follows:
[0044] A. 0.03 g of Ni(OH)2 nanosheets were dissolved in 10 mL of N,N-dimethylformamide (DMF), and then dispersed by ultrasonication and then magnetically stirred at 600 r / min for 30 min to form a Ni(OH)2 solution with a concentration of 3 g / L;
[0045] B. Add 0.6033 g P(VDF-HFP) and 0.3967 g PMMA to the Ni(OH)2 nanosheet solution, stir at 600 r / min magnetic force and 60°C for 2 h, and then stir at room temperature for 4 h to form a pressure-bearing layer solution with a volume ratio of P(VDF-HFP) to PMMA of 50% (the final volume ratio of the two was calculated by dividing the mass by the density);
[0046] C. 0.6953 g P(VDF-HFP) and 0.3047 g PMMA were added to the Ni(OH)2 nanosheet solution, stirred at 600 r / min magnetic force and 60 °C for 2 h, and stirred at room temperature for 4 h to form a buffer layer solution with a volume ratio of P(VDF-HFP) to PMMA of 60%;
[0047] D. P(VDF-HFP) was added to the Ni(OH)2 nanosheet solution, stirred at 600 r / min magnetic force and 60°C for 2 h, and then stirred at room temperature for 4 h to form a polarization layer solution, wherein the amount of Ni(OH)2 nanosheets added to the pressure-bearing layer solution, the buffer layer solution, and the polarization layer solution was 30% by mass;
[0048] E. The pressure-bearing layer solution, buffer layer solution and polarization layer solution were respectively subjected to vacuum treatment to remove bubbles, and electrospun at a rate of 1 mm / min in an environment of temperature 40°C and humidity 30 in the above-mentioned gradient structure order, collected on aluminum foil, and then placed in an oven at 60°C for 2 hours to remove residual solvent to obtain a composite film.
[0049] Step 3: hot pressing to form a film under preset conditions, as follows:
[0050] The composite film prepared in step 2 is pasted on the conductive surface of the conductive glass, and hot-pressed in a vacuum vulcanizer at 150°C and a pressure of 15 MPa for 30 minutes. After the hot pressing, the composite film is placed in an oven at 200°C for 10 minutes, and then quickly placed in an ice-water mixture to complete the quenching operation. After cleaning and drying, a multilayer gradient structured nanocomposite dielectric film is obtained.
[0051] Comparative Example 1
[0052] The same as the above-mentioned Example 1, except that: in step 2C, 0.7802 g of P(VDF-HFP) and 0.2198 g of PMMA are added to the Ni(OH)2 nanosheet solution, stirred at 600 r / min magnetic force and 60°C for 2 h, and then stirred at room temperature for 4 h to form a buffer layer solution with a volume ratio of P(VDF-HFP) to PMMA of 70%.
[0053] Comparative Example 3
[0054] The same as the above-mentioned Example 1, except that: in step 2C, 0.8589 g of P(VDF-HFP) and 0.1411 g of PMMA are added to the Ni(OH)2 nanosheet solution, stirred at 600 r / min magnetic force and 60°C for 2 h, and then stirred at room temperature for 4 h to form a buffer layer solution with a volume ratio of P(VDF-HFP) to PMMA of 80%.
[0055] Comparative Example 4
[0056] The same as the above-mentioned Example 1, except that: in step 2C, 0.9319 g of P(VDF-HFP) and 0.0681 g of PMMA are added to the Ni(OH)2 nanosheet solution, stirred at 600 r / min magnetic force and 60°C for 2 h, and then stirred at room temperature for 4 h to form a buffer layer solution with a volume ratio of P(VDF-HFP) to PMMA of 90%.
[0057] Comparative Example 5
[0058] The same as the above-mentioned embodiment 1, except that the pressure-bearing layer and the buffer layer are completely replaced by laminated bearing, specifically: it includes a symmetrically arranged outer pressure-bearing layer and a polarization layer located between the two pressure-bearing layers, the pressure-bearing layer is a mixture of PMMA (polymethyl methacrylate) and P (VDF-HFP) (polyvinylidene fluoride-hexafluoropropylene copolymer) in an equal volume ratio, the polarization layer is P (VDF-HFP), the pressure-bearing layer, the polarization layer and the buffer layer are all filled with Ni(OH)2, and the thickness of the pressure-bearing layer on one side is equal to the thickness of the polarization layer.
[0059] 2. Experimental Results Analysis
[0060] Figure 1 The preparation flow chart of the multilayer gradient structure composite film. The electrospinning preparation method of the present invention is different from the previous solution casting method, which can reduce the holes and defects of the composite film, make the vertical electric field of the filler in the composite film uniform, and greatly improve the quality of the film. The preparation method basically realizes mechanized operation, which can reduce the impact of human operation errors on the finished film and facilitate actual production application.
[0061] Figure 2 The scanning electron microscope microscopic morphology of the cross section of the multilayer gradient structure composite film. Figure 2 As shown, the cross-sectional morphology of the film prepared in Example 1 has no obvious defects, and there is no obvious difference between the layers, which proves that the preparation method of the gradient composite film of the present invention is very mature. In addition, the introduction of the buffer layer makes the polymer substrate PMMA and P (VDF-HFP) compatible with each other, and there is almost no change in the microstructure. The composite film of the present invention introduces the linear polymer PMMA on the basis of the ferroelectric polymer P (VDF-HFP), which can not only greatly help to improve the breakdown field strength, but also can correspondingly improve the charge and discharge efficiency of the composite material. In addition, the nanosheets filled in the composite film prepared in this embodiment are all distributed in parallel, and this orientation distribution perpendicular to the electric field has a significant hindering effect on the formation of the electrical breakdown path. The microscopic morphology of the multi-layer gradient structure composite film under a scanning electron microscope fully meets the requirements of the film quality required for dielectric capacitors in practical applications, and can improve the energy storage performance.
[0062] Figure 3 The relative dielectric constant of the multilayer gradient structure composite film varies with frequency, and x is the volume percentage of P (VDF-HFP) in the buffer layer. The relative dielectric constants of the different composite films prepared in Example 1 and Comparative Examples 1-5 are characterized, and the differences in dielectric properties are compared. Figure 3 The dielectric properties of these composite films are shown as the frequency changes from 1kHz to 1MHz, which clearly shows good frequency stability. As x increases in Example 1 and Comparative Examples 1-5, the dielectric constant also increases accordingly, which means that the gradient structure of the present invention will produce dielectric differences. This is because when x increases, the P (VDF-HFP) inside the composite film increases, causing the dielectric constant to increase as the gradient difference increases. Compared with Comparative Example 5, the dielectric difference also comes from the change in the interface. The interface polarization generated by the increase in the interface will also cause the dielectric constant to increase.
[0063] Figure 4 The dielectric loss curve of the multilayer gradient structure composite film varies with frequency. The dielectric loss of the gradient structure composite film studied in the present invention varies with frequency in the range of 1kHz to 1MHz. Figure 4 It can be found that the dielectric loss continues to increase with the increase of frequency, which is due to the rapid increase of loss caused by the relaxation behavior of dipole orientation polarization. Overall, the dielectric loss of the gradient structure composite film prepared in Example 1 and Comparative Examples 1-5 is only about 0.03 at 1kHz; at 1MHz, the dielectric loss of Example 1 can still be kept at the lowest (less than 0.1) compared with the comparative example, so the gradient composite film of the present invention can have lower dielectric loss and higher charge and discharge efficiency in a wider frequency range.
[0064] Figure 5 The figure is a bar graph of the breakdown field strength and energy storage density of the multilayer gradient structure composite film. The breakdown resistance and energy storage performance of the multilayer gradient structure composite film prepared in Example 1 and Comparative Examples 1-5 were studied. Figure 5 It can be seen that for the multilayer gradient structure composite film, as the gradient difference increases, the breakdown field strength first increases and then decreases, and the highest field strength is 663.6MV / m when x=60, which is a strong guarantee for achieving high energy storage density. The energy storage density of the multilayer gradient structure composite film prepared in the embodiment and the comparative example is obtained by calculation. As x increases, the energy storage density of the gradient structure composite film first increases and then decreases. When x=60, the composite film has a maximum energy storage density of 25.9J / cm under an electric field of 663.6MV / m. 3 , equivalent to pure P(VDF-HFP) film (9.5J / cm 3) is 273% of that of commercial BOPP film (1.28 J / cm3) and 2023% of that of commercial BOPP film (1.28 J / cm3). It can be seen that the energy storage density can be greatly improved by the gradient structure composite film rationally designed by the present invention.
[0065] Figure 6 The finite element simulation diagram of the electrical breakdown process of the multilayer gradient structure composite film. In order to better explain the mechanism of the gradient structure breakdown path designed by the present invention to enhance the energy storage performance, Figure 7 The finite element simulation of the breakdown path of the gradient structure composite film prepared in Example 1 was performed. Figure 7 It can be observed that the adjacent interfaces of the gradient structure composite film can act as energy barriers to hinder carrier transport, causing electrical trees to develop laterally between the gap layers, thereby delaying the formation of the breakdown path and having an impact on E b There is a significant improvement. In addition, it can be observed that the Ni(OH)2 nanosheets in the composite film are distributed laterally, perpendicular to the direction of the electric field, and as electron scattering centers, they also play a role in hindering the development of the breakdown path. Combining these factors, it can be proved that the multilayer gradient structure composite film of the present invention can achieve excellent breakdown resistance and energy storage performance as shown in the experimental results.
[0066] Figure 7 The finite element simulation diagram of the electric field distribution of the multilayer gradient structure composite film. In order to better explain the mechanism of the electric field distribution of the gradient structure designed in the present invention to enhance the energy storage performance, Figure 8 The finite element simulation of the electric field distribution of the gradient structure composite film prepared in Example 1 was performed. For a multi-layer composite film, the distribution of the electric field depends on the dielectric constant of the adjacent layers. The smaller the dielectric difference, the more uniform the electric field distribution. Figure 8 It can be observed that the buffer layer of the gradient structure composite film of this embodiment makes the electric field distribution of the insulating layer and the polarization layer more uniform, so as to avoid premature breakdown caused by sudden changes in the electric field. This also confirms the original design concept of the present invention, which reduces the dielectric difference between adjacent layers of the composite film through the design of the gradient structure, effectively modulates the uniformity of the electric field distribution, and avoids premature breakdown of the composite film.
[0067] Figure 8 The PE curves of different thicknesses of the pressure-bearing layer and the buffer layer in the multilayer gradient structure composite film are compared. The dielectric constant changes of the pressure-bearing layer and the buffer layer thickness are 2μm:2μm (2-2), 3μm:1μm (3-1), and 1μm:3μm (1-3). When the ratio of the pressure-bearing layer to the buffer layer of the composite film changes from 1:3 to 2:2 and then to 3:1, the dielectric constant becomes lower (the slope reflects the dielectric constant) due to the decrease in the overall content of P (VDF-HFP). Finally, the polarization intensity and breakdown field strength of the composite film reach the highest in the case of 3:1, indicating that the energy storage density is the highest when the ratio of the pressure-bearing layer to the buffer layer is 3:1.
[0068] The above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by a person skilled in the art within the spirit and scope of the present invention shall also fall within the protection scope of the present invention.
Claims
1. A multi-layer gradient structure nanocomposite dielectric film, comprising a symmetrically arranged outer pressure-bearing layer and a polarization layer located between the two pressure-bearing layers, wherein the pressure-bearing layer is a mixture of PMMA and P (VDF-HFP) in an equal volume ratio, and the polarization layer is P (VDF-HFP), characterized in that: A buffer layer is arranged between the pressure-bearing layer and the polarization layer, and the buffer layer is a mixture of P(VDF-HFP) and PMMA in a volume ratio of 60%; the pressure-bearing layer, the polarization layer and the buffer layer are all filled with Ni(OH)2.
2. The multi-layer gradient structure nanocomposite dielectric film according to claim 1, characterized in that: The sum of the thickness of the pressure-bearing layer and the buffer layer on one side is equal to the thickness of the polarization layer.
3. The multi-layer gradient structure nanocomposite dielectric film according to claim 1, characterized in that: The thickness ratio of the pressure-bearing layer to the buffer layer is (1-3): (3-1).
4. The multi-layer gradient structure nanocomposite dielectric film according to claim 1, characterized in that: The thickness ratio of the pressure-bearing layer to the buffer layer is 3:
1.
5. The multi-layer gradient structure nanocomposite dielectric film according to claim 1, characterized in that: The filling mass percentage of the Ni(OH)2 in the pressure-bearing layer, the polarization layer and the buffer layer is 30% respectively.
6. A method for preparing a multi-layer gradient structure nanocomposite dielectric film, characterized in that The following steps are involved: (1) Preparation of Ni(OH)2 nanosheets by hydrothermal method; (2) adding Ni(OH)2 nanosheets to the pressure-bearing layer, the buffer layer and the polarization layer, and performing electrospinning according to the multilayer gradient structure of claim 1; (3) A multilayer gradient structured nanocomposite dielectric film is obtained by hot pressing under preset conditions.
7. The method for preparing a multi-layer gradient structure nanocomposite dielectric film according to claim 6, characterized in that: Step (1) is specifically as follows: 1.2 g NaOH and 3.565 g NiCl2 are weighed and added to 25 ml deionized water respectively, and magnetically stirred at 600 r / min for 30 minutes until completely dissolved, and then the NiCl2 solution is slowly dripped into the NaOH solution and 30 ml deionized water is added to mix, and magnetically stirred at 600 r / min for 30 minutes, and then the uniform mixed solution is poured into a high-pressure reactor, and fully reacted at 200° C. for 24 hours, and the reaction product is washed several times by alternating centrifugation with alcohol and deionized water at a speed of 8000 r / min. After washing, the product is transferred to a vacuum drying oven, dried at 60° C. for 24 hours, and then ground to obtain light green Ni(OH)2 nanosheets.
8. The method for preparing a multi-layer gradient structure nanocomposite dielectric film according to claim 6, characterized in that: Step (2) is as follows: A. Dissolve 1 g of Ni(OH)2 nanosheets in N,N-dimethylformamide (DMF), disperse by ultrasonication, and then stir magnetically at 600 r / min for 30 min until the mixture is uniform, forming a Ni(OH)2 nanosheet solution with a concentration of 0.3 g / L; B. P(VDF-HFP) and PMMA were added to the Ni(OH)2 nanosheet solution, stirred at 600 r / min magnetic force and 60°C for 2 h, and then stirred at room temperature for 4 h to form a pressure-bearing layer solution with a volume ratio of P(VDF-HFP) to PMMA of 50%; C. Add P(VDF-HFP) and PMMA to the Ni(OH)2 nanosheet solution, stir at 600 r / min magnetic force and 60°C for 2 h, and stir at room temperature for 4 h to form a buffer layer solution with a volume ratio of 60%; D. Add P(VDF-HFP) to the Ni(OH)2 nanosheet solution, stir at 600r / min magnetic force and 60℃ for 2h, and stir at room temperature for 4h to form a polarization layer solution; E. The pressure-bearing layer solution, the buffer layer solution and the polarization layer solution are subjected to vacuum treatment to remove bubbles, and are electrospun at a rate of 1 mm / min in an environment of a temperature of 40°C and a humidity of 30°C in the order of the gradient structure described in claim 1, collected on aluminum foil, and then placed in an oven at 60°C for 2 hours to remove residual solvent to obtain a composite film.
9. The method for preparing a multi-layer gradient structure nanocomposite dielectric film according to claim 8, characterized in that: The amount of the Ni(OH)2 nanosheets added to the pressure-bearing layer solution, the buffer layer solution and the polarization layer solution is 30% by mass.
10. The method for preparing a multi-layer gradient structure nanocomposite dielectric film according to claim 6, characterized in that: Step (3) is specifically as follows: pasting the composite film prepared in step (2) on the conductive surface of the conductive glass, and hot pressing it in a vacuum vulcanizer at 150° C. and a pressure of 15 MPa for 30 minutes. After the hot pressing is completed, the composite film is placed in an oven at 200° C. for 10 minutes, and then quickly placed in an ice-water mixture to complete the quenching operation. After washing and drying, a multi-layer gradient structure nanocomposite dielectric film is obtained.
Citation Information
Patent Citations
Preparation method of high energy storage dielectric composite material based on PMMA (poly methyl methacrylatemethacrylic acid) sandwich structure
CN108752612A
All-organic polymer dielectric film with five-layer structure and preparation method of all-organic polymer dielectric film
CN116442596A
Method for preparing high-performance polymer electrolyte by using uniformly dispersed functional nanosheet layer filler
CN118136942A
Co-extruded fluoropolymer multilayer laminates
US20090162652A1
Phase-inversion polymer composite material, fabricating methods and applications of same
US20220243036A1